Breaking negative thinking patterns : a schema therapy self-help and support book - Jacob, Gitta; Genderen, Hannie van.; Seebauer, Laura; Ohio Library and Information Network (Chichester, West Sussex, UK ; Malden, MA : John Wiley & Sons, 2015)
Breaking Negative Thinking Patterns is the first schema-mode focused resource guide aimed at schema therapy patients and self-help readers seeking to understand and overcome negative patterns of thinking and behaviour.-Represents the first resource for general readers on the mode approach to schema therapy -Features a wealth of case studies that serve to clarify schemas and modes and illustrate techniques for overcoming dysfunctional modes and behavior patterns -Offers a series of exercises that readers can immediately apply to real-world challenges and emotional problems as well as the complex difficulties typically tackled with schema therapy -Includes original illustrations that demonstrate the modes and approaches in action, along with 20 self-help mode materials which are also available online -Written by authors closely associated with the development of schema therapy and the schema mode approach
Includes bibliographical references and index
Keywords: Negativism; Schema-focused cognitive therapy; Electronic books